2021
DOI: 10.1016/j.jvoice.2020.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Contact Pressure Between the Vocal Folds in Reinke's Edema: Experimental Observations on an Excised Human Larynx

Abstract: To analyze the range of values of the contact pressure between the membranous vocal folds with Reinke's edema and to compare it to those observed in the absence of such a lesion. Methods. Two human larynges were separately tested on the experimental bench, one of them with a bilateral loose swelling of the vocal folds. Once in a glottal prephonatory configuration, airflow was increased until achievement of self-sustained oscillations while recording aerodynamic, acoustic, electroglottographic data, and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These lesions may be unilateral or bilateral, sessile, swollen with fluid on the vocal cords, and very mobile during phonation. [1][2][3][4] RE is also known as smoking polyp, polypoid laryngitis, polypoid degeneration, and chronic hypertrophic laryngitis. 1.5 It is reported that the prevalence of RE in the general population is less than 1%.…”
Section: Introductionmentioning
confidence: 99%
“…These lesions may be unilateral or bilateral, sessile, swollen with fluid on the vocal cords, and very mobile during phonation. [1][2][3][4] RE is also known as smoking polyp, polypoid laryngitis, polypoid degeneration, and chronic hypertrophic laryngitis. 1.5 It is reported that the prevalence of RE in the general population is less than 1%.…”
Section: Introductionmentioning
confidence: 99%